Controlling the microstructure of the porous nickel electrodes in alkaline electrolysers - Serdaroglu, Gulcan (2018)
Ni-based electrodes have been extensively studied for hydrogen evolution reaction (HER) in alkaline electrolysers in an attempt to improve its electrocatalytic activity through alloying it with other metals and/or increasing the surface area. However, the role of microstructure on the electrochemical performance has received little attention. In this study, Ni-based catalysts have been prepared by a powder metallurgy technique including compaction and sintering of a mixture of Ni, starting alloy (consisting of Al3Ni and Al3Ni2) and binder. As-sintered samples were then treated in concentrated alkaline solution for leaching of Al. The microstructural properties are controlled by changing the parameters of the preparation process; i.e. sintering temperature, starting alloy to Ni ratio, leaching temperature and binder properties (concentration and particle size). Increasing the sintering temperature from 625 to 900 °C improved the mechanical strength but also increased the diffusion of Al from Al-rich phases into Ni, resulting in reduced Al-rich phases available after sintering. Since Al can only be leached from Al-rich phases, the specific surface area of micro- and mesopores (with the latter having a size range of 2-14 nm) created during the leaching reduced by almost 90 % from 625 to 900 °C sintering temperature. Although there was a ca. 15 times increase in the specific surface area by increasing the starting alloy concentration from 0 to 60 wt.%, the robustness of catalysts reduced since the compressibility of alloy powder is lower than that of Ni, resulting in increased macroporosity. This suggests that the starting alloy concentration should be in the range of 20-40 wt.% in order to achieve relatively robust and inexpensive porous catalysts without compromising too much the surface area. N2 sorption isotherms showed that leaching at 30 and 50 °C resulted in pores with a slit shape, whilst leaching at 60, 70 and 80 °C lead to ink-bottle pores. This was attributed to increasing leaching rate with higher leaching temperatures in comparison to speed of atomic rearrangement at the surface. Increasing the leaching temperature from 30 to 60 °C improved the specific surface area by almost 4 times, whilst leaching at 60, 70 and 80 °C gave similar surface areas. Greater binder concentrations led to increased macroporosity and surface roughness as well as greater numbers of windows between the adjacent cavities. Consequently, the mechanical strength of porous catalysts reduced due to the decrease in the wall thickness. It was also found that the size of the binder particles influences the robustness of the porous catalysts, with the smaller the binder size the greater the robustness. The comparison of trends in alkaline electrolyser cell voltage and compositional and microstructural properties showed that the surface area has a dominant effect on the electrocatalytic activity for HER in comparison to the composition of Ni-based electrodes. Despite greater Al contents, the cell voltage still decreased with increasing surface areas (with micropores accounting for ca. 80 %). However, it was found that the effective use of micro- and mesopores depends on the pore morphology, with slit-shaped pores being more effectively used during HER in comparison to ink-bottle pores which can be more subject to mass transport limitation. It was shown that H2 bubbles cannot form inside the micro- and mesopores, therefore generated H2 can only leave the pores through diffusion which appears to be favoured by a slit shape in comparison to ink-bottles. It was also found that increasing the amount of large macropores (> 15 µm) is not advantageous to the production of electrodes for alkaline electrolysers as it results in increased electrode thickness and reduced mechanical strength with no measureable improvement in electrochemical performance.